Notes for the Analysis of Adolescent and Youth Dating Violence - Yamila Ramos Rangel; Laura Magda López Angulo; María Suz Pompa (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
The multiplicity of forms of expression of violence is increasingly present in individual, relational, community, global daily life with an immense capacity to express itself both explicitly and subtle. Within these types of abuse, one that particularly impacts the adolescent and youth population is dating violence. The objective of this work is to analyze some particularities of dating violence and the urgent need for its approach.